La loi sur l’abolition de la retraite obligatoire - Garcia, Claude (Assurances)

(untitled) (HEC Montréal, 1982)
Should retirement be compulsory from a certain age? The question has now been answered in Quebec by Bill 15, which took effect on April 1st 1982. Mr. Claude Garcia, actuary, studies the provisions of the new law and its consequences.